Effect of atmospheric turbulence on orbital angular momentum entangled state. (21st January 2022) - Yan, Xiang; Zhang, Peng-Fei; Fan, Cheng-Yu; Zhang, Jing-Hui
Abstract: The entangled orbital angular momentum (OAM) photons propagating across a weakly turbulent atmosphere are investigated. Here, the paper uses the single-phase screen model based on the Kolmogorov theory of turbulence, and focuses on the influence of the backward scattering on OAM evolution. The results indicate that backward scattering plays an important role in the analysis of OAM entanglement evolution in the turbulent atmosphere. It cannot be negligible especially for higher-order OAM mode. Moreover, when OAM mode is greater than 4, entangled photon pairs composed of higher OAM modes are not more robust in turbulence within the weak scintillation regime. These results will be useful in future investigations of OAM-based optical wave propagation through turbulent atmosphere.